2005
DOI: 10.1258/0956462053420158
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with participation by HIV-1-positive pregnant women in an intervention to prevent mother-to-child transmission of HIV in Côte d'Ivoire

Abstract: Many HIV-1-seropositive women in Africa who are offered antiretroviral prophylaxis to prevent mother-to-child transmission (MTCT) of HIV do not begin interventions. Research on barriers to participation has not addressed the possible effects of women's sociocultural and economic circumstances. We examined these factors at an MTCT prevention programme in Abidjan, Cote d'Ivoire. We interviewed two groups of women after they had received HIV-positive test results and had been invited by the programme staff to ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 11 publications
2
45
1
Order By: Relevance
“…The small sample size and purposeful sampling methodology may also limit our ability to generalize to the HIV population in Mozambique. Nonetheless, the voices and life circumstances of those who participated in our study were consistent with the findings of other studies, and provide valuable insights that allow us to better understand reasons for poor follow-up that may apply to women and children in similar contexts (Chapman, 2003(Chapman, , 2006Farmer, Leandre, et al, 2001;Jones et al, 2005;Painter et al, 2004;Painter et al, 2005).In conclusion, our study's findings suggest that the mere provision of clinical HIV care services will not necessarily engage HIV/AIDS-affected women and children into medical care. Our observed LTFU of more than 50% of infants (Blankenship et al, 2000) appeared to be associated with mothers' daily struggles related to poverty and food insecurity, which prevented their use of available services.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The small sample size and purposeful sampling methodology may also limit our ability to generalize to the HIV population in Mozambique. Nonetheless, the voices and life circumstances of those who participated in our study were consistent with the findings of other studies, and provide valuable insights that allow us to better understand reasons for poor follow-up that may apply to women and children in similar contexts (Chapman, 2003(Chapman, , 2006Farmer, Leandre, et al, 2001;Jones et al, 2005;Painter et al, 2004;Painter et al, 2005).In conclusion, our study's findings suggest that the mere provision of clinical HIV care services will not necessarily engage HIV/AIDS-affected women and children into medical care. Our observed LTFU of more than 50% of infants (Blankenship et al, 2000) appeared to be associated with mothers' daily struggles related to poverty and food insecurity, which prevented their use of available services.…”
supporting
confidence: 85%
“…HIV/AIDS, loss to follow-up, adherence, HIV care, access barriers 2 SAGE Open Maman, 2007;Manzi et al, 2005;Painter et al, 2005). Finally, structural factors, including the physical, social, cultural, organizational, community, economic, or policy aspects of the environment, can act as barriers or facilitators to individually oriented HIV prevention and care services (Blankenship, Bray, & Merson, 2000;Farmer, 2004;Farmer, Leandre, et al, 2001;Gupta, Parkhurst, Ogden, Aggleton, & Mahal, 2008;Jones et al, 2005;Parker, Easton, & Klein, 2000;Sumartojo, Doll, Holtgrave, Gayle, & Merson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The clinics were selected to reflect different socio-economic profiles, rural-urban settings and size of patient load, factors that have been shown to affect women's PMTCT participation in Côte d'Ivoire and South Africa. 6,11,12 Site A, semi-urban, served over 174,000 people, provided antenatal care to 11.5% of pregnant women in Lilongwe and conducted approximately 3,000 deliveries annually. Site B, rural, served over 100,000 people and provided antenatal care to 6.5% of pregnant women in Lilongwe.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that improving women's access to prenatal care improves PMTCT uptake [81] . Several studies have identified certain obstetric factors, such as bad obstetric history, or being multi gravida vs primigravida, as associated with uptake of VCT [41,63,65,67,82] . It is possible that multigravida women had more contact with prenatal care services and therefore had prior experience of HIV testing, or that they were more aware of the MTCT of HIV.…”
Section: Knowledge Perceived Susceptibility To Hiv and Perceived Bementioning
confidence: 99%
“…Studies have also found that lack of confidentiality was associated with less participation in HCT [31,42,56,97] . Negative experiences with medical personnel [55,82] , as well as low quality of pre-test counseling, were also associated with less participation in HCT [66,95,96] . In addition, women's failure to understand the HIV testing procedure as explained during group counseling, as well as dislike for group counseling, were listed among the major reasons for refusing the test [31] .…”
Section: Health Care Provider Related Factorsmentioning
confidence: 99%